Acute Generalized Exanthematous Pustulosis Due to Cephalexin: A Case Report and Literature Review - Shirin Sheibani; Mahdie Sadat Mousavi; Hamed Jafarpour; Javad Ghaffari; Abbas Dabbaghzadeh; Salar Behzadnia (Mazandaran University of Medical Sciences, 2021)
Introduction: Acute Generalized Exanthematous Pustulosis (AGEP) is a cutaneous reaction that may appear after using certain medications, such as cephalexin. This disease is characterized by non-follicular sterile pustules, erythematous, urticaria, fever over , and leukocytosis. Cephalexin belongs to the family of β-lactam antibiotics, which are widely used to treat infections. However, cephalexin skin sensitivities have been reported rarely. Herein, in this case, we aimed to report a patient presented with AGEP due to cephalexin usage. Case Presentation: A 12-year-old boy presented with warm skin lesions that gradually appeared on the limbs, trunk, face, and neck after using cephalexin powder on his left leg injury. Because of his symptoms, acetaminophen, fexofenadine hydrochloride, loxoprofen sodium, and ointment, including difluprednate and hydrocortisone, were prescribed. Over time, the patient's fever subsided, and 8 days later, the symptoms of AGEP, including urticaria, erythematous, and pustules in the neck and trunk, disappeared. Conclusions: Cephalexin is one of the antibiotics that doctors and patients consider when there is a possibility of infection. AGEP is a rare but severe reaction that can manifest as skin rashes in any age and sex following the use of cephalexin, so the patient should be careful when using this antibiotic.